2016
DOI: 10.1590/1981-7746-sip00098
|View full text |Cite
|
Sign up to set email alerts
|

Competências Andragógicas Dos Docentes Enfermeiros Que Atuam Na Graduação Em Enfermagem Paulistana

Abstract: Resumo O objetivo foi avaliar o nível de desempenho do enfermeiro docente nas competências essenciais para a educação de adultos, na perspectiva andragógica. Estudo descritivo, comparativo, transversal, quantitativo, foi desenvolvido com 226 docentes enfermeiros que atuavam em vinte cursos de graduação em enfermagem. Utilizou-se estatística descritiva, testes não paramétricos e software Minitab® 16. A população tinha predominantemente entre 46-55 anos, era majoritariamente do gênero feminino, formou-se em esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…A study, carried out with nursing undergraduate teachers, had compared with the sample of this study the majority of female participants who worked both in theoretical and practical classes and worked in a workload of 30 to 40 hours per week, but with regard to the training of teachers who work at the higher level, it was observed a higher percentage of specialists, masters and doctors. 7,10,11 Thus, it is evident that the teachers in the area of nursing, especially those who participated in this study who act in the medium level, has a profile of experience in teaching being mostly specialists, acting in theoretical and practical classes and with experience and knowledge of practice. This professional profile is generally recommended to act in a medium level course, mainly in what concerns the experience in the practice, because it is relevant that the teacher has knowledge of the practice to teach the students of a technical nursing course.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A study, carried out with nursing undergraduate teachers, had compared with the sample of this study the majority of female participants who worked both in theoretical and practical classes and worked in a workload of 30 to 40 hours per week, but with regard to the training of teachers who work at the higher level, it was observed a higher percentage of specialists, masters and doctors. 7,10,11 Thus, it is evident that the teachers in the area of nursing, especially those who participated in this study who act in the medium level, has a profile of experience in teaching being mostly specialists, acting in theoretical and practical classes and with experience and knowledge of practice. This professional profile is generally recommended to act in a medium level course, mainly in what concerns the experience in the practice, because it is relevant that the teacher has knowledge of the practice to teach the students of a technical nursing course.…”
Section: Discussionmentioning
confidence: 91%
“…In general, the focus on the teaching and learning process and the use of methodological resources are not usual in the practice of teachers who have learned to value theoretical content 7 Thus, for teachers who work at the secondary level it becomes even more challenging to develop skills to work with adults considering the professional education in which it is relevant to have the knowledge of the practice and, therefore, one should know how to do and teach. 14 Compared to the results of the study with the nursing undergraduate teachers, 7,10,11 after the analysis of the four domains present in the competence "Facilitator of learning", it was identified that the teachers of the technical level were more qualified in all the items that compose the four domains, as well as the teachers of the superior level demonstrated greater desire for development in 24 of the 29 items present.…”
Section: Andragogical Skills At the Nursing Technician Levelmentioning
confidence: 91%
See 2 more Smart Citations
“…This analysis permitted the PM to be construed as a tool in the development of the teaching/learning process during the training of nurses oriented to PHC teaching. It is noteworthy that in Brazil undergraduate nursing courses are still ruled by the traditional paradigm, in which innovative strategies are infrequent (24)(25)(26)(27)(28)(29) .…”
Section: Discussionmentioning
confidence: 99%